Association between oral health care behavior and quality of life in elderly with diabetes mellitus in Menur Public Health Center, Surabaya - Setijanto, R. Darmawan; Adhiningtyas, Aldila Putri; Yuliantoro, Rahmad; Herrifnasari, Alifiya Mei; Voletta, Raniah Salma; Mahrunisa, Ammara Nabiila; Hidayat, Marvin; Hemadi, Abdullah Sherf; Yuristra, Frinsky Smartura; Nurfitri, Aisyah Qonita (Indonesian Journal of Dental Medicine, 2024)
Background: An elderly person is someone who is more than 60 years old. In Indonesia, there is an increase in the elderly population, increasing the prevalence of non-communicable diseases such as diabetes mellitus. Diabetes mellitus is an abnormal increase in blood glucose. In Indonesia, the prevalence of diabetes mellitus in 2018 was 2%. Diabetes mellitus causes various complications in the body, one of which is the oral cavity, which can affect quality of life. Purpose: To analyze the relationship between oral health care behavior and the quality of life of elderly patients with diabetes mellitus in the Menur Surabaya Community Health Center. Methods: The study was conducted with analytic observation and a cross-sectional approach on 80 elderly people with diabetes mellitus in the Menur Community Health Center. The data were obtained using a questionnaire. The data were tested for normality using the Kolmogorov-Smirnov method, and then correlation was tested using Spearman rank correlation. Results: There is a significant relationship between perceived barriers, self-efficacy, and cues to action towards oral health behavior. However, there is no significant relationship between perceived susceptibility, perceived severity, perceived benefits, and quality of life towards oral health behavior. Conclusion: Quality of life hinges on oral health behavior, yet correlation tests reveal no significant link between oral health care and quality of life for diabetes patients, who prioritize other health facets. Age also impacts, with elders prioritizing aesthetics less than youth.